Association between Cardiac Enzymes Level in Type 2 Diabetes Mellitus from Jazan Region, Saudi Arabia - Mohammad Shane Alam ,Yahia A. Kaabi , Md. Mazharul Hoque,Farhana Riyaz Shah,Muhammad H. Khawaji , Mohammad Suhail Akhter,Zaki H Hakami, Yahia Mjery (South Eastern European Journal of Public Health, 2025)
Diabetes mellitus is characterized by deficiencies in insulin secretion and action, often leading to complications such as cardiac dysfunction associated with insulin-resistance syndrome. This study aimed to investigate the associations between serum cardiac enzyme levels (lactate dehydrogenase [LDH] and creatine kinase-MB [CK-MB]) and the incidence of type 2 diabetes mellitus in the Jazan population. Conducted at the MLT-Biochemistry laboratory of the College of Applied Medical Sciences, Jazan University, Saudi Arabia, the study involved the collection of 5 ml blood samples from 55 patients with type 2 diabetes and 35 control subjects. The mean (±S.D.) levels of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in the control group were found to be 12.13±0.70 and 17.47±0.70 U/L, respectively, while in diabetic patients, the levels were significantly elevated at 20.55±1.90 and 24.15±2.10 U/L. Statistical analysis revealed significant differences in the means of ALT and AST levels between the two groups. The findings indicate that individuals with type 2 diabetes exhibit markedly higher serum liver enzyme levels compared to non-diabetic individuals, highlighting a greater incidence of liver function test (LFT) abnormalities in diabetic subjects. This study underscores the need for monitoring liver enzyme levels in patients with type 2 diabetes to better understand the associated risks and complications.